2006
DOI: 10.1068/c0436
|View full text |Cite
|
Sign up to set email alerts
|

Should Government be Stimulating Start-ups? An Assessment of the Scope for Public Intervention in New Venture Formation

Abstract: An overview of policy thinking on start-ups: context and drivers of public assistance for new venture creation There is broad agreement at a policy level that new business creation is an integral component of an entrepreneurial and dynamic economy (DTI, 2001; EC, 2003; OECD, 1998; Reynolds et al, 2000). Start-ups and self-employment are seen as important sources of new wealth and jobs, as well as a means of enhancing overall competitiveness as entrants seek out and create new business opportunities and activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 49 publications
(34 reference statements)
1
27
0
Order By: Relevance
“…As a result, many of the assumptions and findings from the very early HGF literature, even dating back to David Birch's seminal studies in the 1970s and 80s (Birch, 1979;1981), have continued to dominate policy discourse and development, despite new (and sometimes contradictory) findings emerging. An example of this is the continued focus by policy makers on start-ups generally, despite the evidence showing most start-ups generate little in the way of economic value commensurate with the value of the support they receive (Atherton 2006;Shane 2009;Fritsch and Storey 2014;Mason and Brown, 2014).…”
Section: Recent High Growth Firm Literaturementioning
confidence: 99%
“…As a result, many of the assumptions and findings from the very early HGF literature, even dating back to David Birch's seminal studies in the 1970s and 80s (Birch, 1979;1981), have continued to dominate policy discourse and development, despite new (and sometimes contradictory) findings emerging. An example of this is the continued focus by policy makers on start-ups generally, despite the evidence showing most start-ups generate little in the way of economic value commensurate with the value of the support they receive (Atherton 2006;Shane 2009;Fritsch and Storey 2014;Mason and Brown, 2014).…”
Section: Recent High Growth Firm Literaturementioning
confidence: 99%
“…Blanden et al 2005;Minniti and Lévesque 2008;Frankish et al, 2014). Hence, promotion of business start-ups has remained a key agenda item for the economic development policy of most of the developed and developing nations (Atherton 2006;Storey 2003). At the same time, in some regions, high rates of new firms' creation may represent clusters of low value added, low dynamism activities (Van Stel and Storey 2004).…”
Section: Introductionmentioning
confidence: 99%
“…It seems more likely that viable SMEs are a result of broader economic development and therefore are not a suitable policy vehicle to stimulate growth. There are also question marks about the feasibility of intervening in start ups (Atherton 2006), especially since some studies show that 81 % of small businesses do not even have the desire to grow (Van Gelderen et al 2005, p.19). Little et al (1987) found that SMEs are no better at job creation than large firms, and firm-level analysis finds that SMEs aren't particular effective job creators.…”
Section: On Entrepreneurshipmentioning
confidence: 98%